Gender moderates the effect of darkness on ethical behaviors: An explanation of disinhibition. (1st August 2018) - Liu, Guofang; Niu, Xiaoxiao; Lin, Lin
Abstract: The relationship between darkness and ethical behaviors is confusing. The mixed findings may be explained by the general process of disinhibition. In this view, gender may moderate the effect of darkness on ethical behaviors. The results of two experiments support this prediction. In Experiment 1, male participants in dimly lit streets exhibited lower levels of prosocial behaviors than those in well-lit streets, whereas women in dimly lit streets exhibited significantly higher levels of prosocial behaviors than those in well-lit streets. In Experiment 2, male college students in a dimly lit room exhibited significantly lower levels of trustworthiness in a trust game than those in a well-lit room, whereas there was no significant difference between the trustworthiness levels of women in rooms with varying levels of illumination; Experiment 2 also revealed that darkness did not affect participants' trust. In summary, gender moderates the effect of darkness on ethical and prosocial behaviors. Highlights: Gender moderates the effect of darkness on ethical behaviors. Darkness decreases men's trustworthiness but increases women's. Darkness decreases men's prosocial behaviors but increases women's.